Chronicling moral distress among healthcare providers during the COVID‐19 pandemic: A longitudinal analysis of mental health strain, burnout, and maladaptive coping behaviours. (13th October 2021) - Wilson, Chloe A.; Metwally, Hannah; Heavner, Smith; Kennedy, Ann Blair; Britt, Thomas W.
Abstract: The COVID‐19 pandemic has presented many novel situations that have amplified the presence of moral distress in healthcare. With limited resources to protect themselves against the virus and strict safety regulations that alter the way they work, healthcare providers have felt forced to engage in work behaviours that conflicted with their professional and personal sense of right and wrong. Although many providers have experienced moral distress while being physically in the workplace, others suffered while at home. Some healthcare providers worked in facilities that were unable to open during the pandemic due to restrictions, which could contribute to a sense of powerlessness and guilt. The current study assessed whether the ability to see patients each week impacted the relationship between an employee's moral distress and their mental health strain, burnout, and maladaptive coping. A total of 378 healthcare providers responded to weekly surveys over the course of 7 months (April 2020–December 2020). Hierarchical linear modeling techniques were used to examine the study variables over time. Results showed that moral distress predicted an individual's mental health strain and burnout, even after controlling for the prior week. However, moral distress was not a significant predictor of maladaptive coping. Interestingly, there was not a significant difference between the average ratings of moral distress between those who were able, and those who were not able to see patients, meaning that both groups experienced symptoms of moral distress. However, cross‐level moderation results indicated that the ability to see patients magnified the relationships between moral distress and mental health strain and burnout over time. Implications of the results and recommendations for how moral distress should be addressed among healthcare providers are discussed.